2015
DOI: 10.1117/1.jbo.20.3.037009
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral autoregulation in the preterm newborn using near-infrared spectroscopy: a comparison of time-domain and frequency-domain analyses

Abstract: Abstract. The aim was to compare two conventional methods used to describe cerebral autoregulation (CA): frequency-domain analysis and time-domain analysis. We measured cerebral oxygenation (as a surrogate for cerebral blood flow) and mean arterial blood pressure (MAP) in 60 preterm infants. In the frequency domain, outcome variables were coherence and gain, whereas the cerebral oximetry index (COx) and the regression coefficient were the outcome variables in the time domain. Correlation between coherence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
2
18
0
2
Order By: Relevance
“…More recent studies have focussed on the use of NIRS to assess cerebral autoregulation in neonates, see for example Caicedo et al (2011a), Eriksen et al (2015). It has been shown that there are few differences between different NIRS metrics, indicating that a range of such metrics can be used to assess autoregulation, Caicedo et al (2011b), although interpretation of any of these metrics needs to be done with care.…”
Section: Neonatesmentioning
confidence: 99%
“…More recent studies have focussed on the use of NIRS to assess cerebral autoregulation in neonates, see for example Caicedo et al (2011a), Eriksen et al (2015). It has been shown that there are few differences between different NIRS metrics, indicating that a range of such metrics can be used to assess autoregulation, Caicedo et al (2011b), although interpretation of any of these metrics needs to be done with care.…”
Section: Neonatesmentioning
confidence: 99%
“…In the frequency-domain analysis, they used the variables coherence and gain, and for the time-domain analysis, they used COx in 60 very preterm infants (GA 26.6 ± 1.3 weeks). They found that the concordance between the two methods was poor: the two methods did not classify the same infants as having intact or impaired cerebrovascular autoregulation [76].…”
Section: Time-domain Versus Frequency-domain Analysismentioning
confidence: 99%
“…Fundamental limitations of CW fNIRS are difficult to overcome without high density optode arrangements and innovative signal processing. FD fNIRS requires slightly more complex instrumentation with a frequency modulated source and phase-locked detector, but it is able to quantify absolute concentration of chromophores and can image deeper than CW [18,19]. TD fNIRS requires the most complex instrumentation due to the need for picosecond time gating on each detector, but it also has the most promise for high resolution imaging of chromophore concentration [20,21].…”
Section: Introductionmentioning
confidence: 99%